The Archive of the Kingdom of Valencia (1419-2019). Six hundred years of history - Francesc Torres Faus Torres Faus (Catalan Historical Review, 2022)
The Arxiu Reial de València (Royal Archive of Valencia) was created in 1419 and was housed in the Palau Reial (Royal Palace). At first it was managed by an archivist appointed by the monarch, but in 1579 the profession of archivist was added as an assistant of the Master Rational (magister racionalis), and it depended on this institution until 1707. During the era of foralism, it housed the collections of the Cancelleria Reial (Royal Chancery), the Reial Audiència (Royal Court), the Master Rational and the Corts Valencianes (the legislative body of Valencia). After 1707, when the local regime in Valencia was abolished, the monarchs ordered the documentation from the abolished institutions to be assembled together. This did not actually occur until the nineteenth century, when the Royal Palace was demolished in 1810 and the archive was moved to the Casa Professa of the Jesuits. The archives of the Generalitat, the Governate, the Justices of the city of Valencia and the Batlia (Bailiff) were transferred there. In the twentieth century, the documentation from the Bourbon era was moved there, and in 1965 the Arxiu del Regne de València (Archive of the Kingdom of Valencia) was moved to its current location.